Student Loan Debt, Family Support, and Reciprocity in the Transition to Adulthood. Issue 6 (December 2022) - Mazelis, Joan Maya; Kuperberg, Arielle
This study explores student loans, family support, and reciprocity during the transition out of college into adulthood. We examine experiences of family financial assistance and co-living among college students and graduates with loans, and whether support and reciprocity systematically differed by loan presence. We conducted four waves of qualitative interviews with college graduates with loans at two public universities, in their senior year and annually for three years after graduation ( N =24 participants, 72 interviews), and collected two rounds of survey data with undergraduates ( N =3251) and graduates 15 months after graduation ( N =176) from the same universities. Financial support from and living with family was common. Those with loans gave more money to family, even when they did not live with them. Interviews revealed that reciprocity, or expectations to help family in return for help received, could be burdensome. Findings indicate that receiving help may prolong—but also facilitate—the transition to adulthood.